PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN (STUDI PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA TAHUN 2009 – 2013) - Sera, Pinta Nopetri; Kamaliah, Kamaliah; Desmiyawati, Desmiyawati (Jurnal Ekonomi, 2016)
This research intends to identify and analyze the effect of Intellectual Capital VACA, VAHU, STVA and ROGIC to financial performance ROE, EPS and ASR in LQ45 Company Listed at Indonesia Stock Exchange. Population in this research are all companies incorporated in LQ45 at Indonesia Stock Exchange (BEI). In accordance with BEI publication indicates that the number of listed companies in LQ45 is 45. Sampling in this research used purposive sampling method, and the sample result is 22 company incorporated in LQ45. All data in this research was data obtained from financial statements in LQ45. The analysis was done by using multiple regression supported by SPSS version 21.0. This research have 12 hypothesis, and the result of this research show that VACA and STVA has significant effect on ROE and EPS, and then VAHU and ROGIC has significant effect on ASR.